2022
DOI: 10.1016/j.cgh.2020.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Perianal Crohn's Disease: Long-term Follow-up of a Population-Based Cohort

Abstract: Marie-Laure RABILLOUD and Emma BAJEUX declare no conflict of interest Acknowledgments: All physicians who included patients in the ABERMAD registry particularly to Etienne Cruchant, Jean-Luc Alexandre et Jacques-Arnaud Seyrig members of the scientific committee of ABERMAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…perianal CD varied between 11% and 19% at 1-10 years after diagnosis. 9 In a study of 983 patients with CD in Asia, stricturing or penetrating CD occurred in 41% and perianal disease in 25% of patients. 10 At the other end of the spectrum, incidental terminal ileitis can be diagnosed in 1.6% of individuals undergoing nondiagnostic colonoscopy, with an uncertain but likely low rate of progression to overt CD.…”
mentioning
confidence: 99%
“…perianal CD varied between 11% and 19% at 1-10 years after diagnosis. 9 In a study of 983 patients with CD in Asia, stricturing or penetrating CD occurred in 41% and perianal disease in 25% of patients. 10 At the other end of the spectrum, incidental terminal ileitis can be diagnosed in 1.6% of individuals undergoing nondiagnostic colonoscopy, with an uncertain but likely low rate of progression to overt CD.…”
mentioning
confidence: 99%
“…Several studies have attempted to identify risk factors associated with CD-PAF. Colonic disease, especially rectal involvement, younger age at diagnosis, male sex, longer disease duration of CD, and extraintestinal manifestations have been associated with higher rates of CD-PAF (4,13,14). Emerging data have demonstrated that the use of corticosteroids is associated with an increased risk of PAF in CD, and early use of steroid-sparing therapy is associated with a decreased risk of PAF and fistula complications (15,16).…”
Section: Pathogenesismentioning
confidence: 99%
“…Fistulizing perianal disease is found in up to 25% of patients with Crohn's disease during their disease course (1)(2)(3). An additional 10% of patients have other perianal manifestations including fissures, stenosis, and skin tags.…”
Section: Introductionmentioning
confidence: 99%
“…A fistula is a common complication and aggressive phenotype of Crohn’s disease (CD) that affects approximately 30% of patients during their disease course [ 1 , 2 , 3 ]. Fistulas in CD can be classified into internal and external fistulas.…”
Section: Introductionmentioning
confidence: 99%